Analysis of the internalization of society and the transition to new marketing tools ("Journal "U". Economy. Management. Finance.", 2024)
With the development of digital technologies and social networks, companies are faced with the need to adapt their marketing strategies to new conditions. The internetization of society and the transition to new marketing tools require companies to constantly develop and adapt to changing market conditions. Understanding the needs of digital consumers, creating customized solutions and improving content are becoming key success factors in modern marketing.
Keywords: marketing; marketing tools; buyer; Internet